Alpha Lipoic Acid Alleviates Oxidative Stress and Preserves Blood Brain Permeability in Rats with Subarachnoid Hemorrhage - YEGEN, BERRAK; ERZİK, CAN; YÜKSEL, MERAL; ÇETİNEL, ŞULE (SPRINGER/PLENUM PUBLISHERS, 2010)
The neuroprotective effect of alpha lipoic acid (ALA; 100 mg/kg, po), a dithiol antioxidant, on experimentally induced subarachnoid hemorrhage (SAH) was assessed in Wistar albino rats. Neurological examination scores recorded at the 48th h of SAH induction were increased in SAH groups, which were accompanied with significant increases in the formation of reactive oxygen species, DNA fragmentation ratios, malondialdehyde levels and myeloperoxidase activity, while significant decreases in the brain glutathione content and Na+, K+-ATPase activity were observed. On the other hand, ALA treatment reversed all these biochemical indices as well as SAH-induced histopathological alterations. Increased brain edema, impaired blood-brain-barrier permeability and neurological scores were also improved by ALA treatment. The results demonstrate that ALA exerts neuroprotective effects via the enhancement of endogenous antioxidant enzyme activity, the inhibition of neutrophil accumulation and free radical generation, suggesting a therapeutic potential in reducing secondary injury after SAH in patients.
Keywords: Alpha lipoic acid; Antioxidant; Cerebral vasospasm; Subarachnoid hemorrhage; Lipid peroxidation; ENDOTHELIAL DYSFUNCTION; RADICAL SCAVENGER; REACTIVE OXYGEN; INTRACELLULAR GLUTATHIONE; NA+,K+-ATPASE ACTIVITY; CEREBRAL VASOSPASM; LIPID-PEROXIDATION; DOUBLE-BLIND; CELL-DEATH; INJURY